Advancements in the study of transition metal oxide bifunctional catalysts for rechargeable zinc−air batteries - Jianfang LIU; Yongzhi ZHAO; Yong WANG; Luan LIU; Sijia LIU; Yunpu QIN; Haoyang WU; Deyin ZHANG; Baorui JIA; Xuanhui QU; Mingli QIN (工程科学学报, 2024)
In recent years, rechargeable zinc–air batteries (ZABs) have attracted much attention owing to their high theoretical specific energy density, safety, and environmental friendliness. They are also considered a viable option for powering the grid and electric vehicles in the future. The activity and the stability of the bifunctional catalysts for the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) in ZABs remarkably influence the battery’s energy, power densities, and lifetime. Therefore, developing efficient and stable bifunctional catalysts is an important research direction. Previously, precious metal catalysts such as Pt/C, Ir/C, and Ru/C have been used to design efficient ORR and OER electrocatalysts. However, these electrocatalysts possess several issues, including limited natural abundance, high metal sintering and catalyst detachment rates from supports, and poor bifunctional activity, which limit their practical applications. As potential catalysts, nonprecious transition metal oxides exhibit the prominent advantages of manifold compositions, multiple valence states, environmental friendliness, high durability and abundance, and varying structures. Their disadvantages include poor electrical conductivity and a limited surface area. To address the abovementioned issues, current general research focuses on compounding transition metal oxides with carbon materials or other conductive substrates to simultaneously increase their specific surface area and electrical conductivity and control their morphology to expose more active sites. Furthermore, the intrinsic activity of the transition metal oxides must also be regulated through the most commonly used activity regulation methods (e.g., heteroatom doping and defect engineering). For example, perovskite and spinel-type transition metal oxides must meet a specific eg orbital occupancy to achieve the best bifunctional activity. Therefore, improving the catalytic performance requires the A- and B-site atom substitution with other alkaline and rare earth or transition metals or the introduction of oxygen vacancies to adjust the electronic structure. Spinel- and perovskite-type transition metals and manganese oxides are the research objects used in this work. The activity sources of different types of transition metal oxide catalysts and their performances in energy density, charge/discharge voltage, and cycle life of zinc–air batteries are introduced herein. The strategies and methods used to improve the catalytic performance of transition metal oxides in current research are summarized. Finally, the future development of transition metal bifunctional catalysts for oxygen reduction and evolution reactions is prospected.